2012
DOI: 10.1126/science.1225748
|View full text |Cite
|
Sign up to set email alerts
|

Corals Chemically Cue Mutualistic Fishes to Remove Competing Seaweeds

Abstract: Corals in the genus Acropora generate much of the structural complexity upon which coral reefs depend, but they are susceptible to damage from toxic seaweeds. Acropora nasuta minimizes this damage by chemically cuing symbiotic goby fishes (Gobiodon histrio or Paragobiodon echinocephalus) to remove the toxic seaweed Chlorodesmis fastigiata. Within minutes of seaweed contact, or contact from only seaweed chemical extract, the coral releases an odor that recruits gobies to trim the seaweed and dramatically reduce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
57
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(57 citation statements)
references
References 33 publications
0
57
0
Order By: Relevance
“…Very similar values were obtained for the apogonids Apogon fragilis Smith (mean of 100 s), Ostorhinchus nigrofasciatus (Lachner) (66–143 s) and Nectamia similis Fraser (65–162 s) (Schubert et al . ; Dixson & Hay ). These relatively constant and high levels of toxicity suggest that predation pressure is generally high for coral gobies.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Very similar values were obtained for the apogonids Apogon fragilis Smith (mean of 100 s), Ostorhinchus nigrofasciatus (Lachner) (66–143 s) and Nectamia similis Fraser (65–162 s) (Schubert et al . ; Dixson & Hay ). These relatively constant and high levels of toxicity suggest that predation pressure is generally high for coral gobies.…”
Section: Discussionmentioning
confidence: 99%
“…Different toxicity levels of the same species may reflect regional differences. The toxicity of gobies may also be enhanced by the ingestion of toxic algae (Dixson & Hay ). Additionally, the rapid drop in toxicity over time may play a role: our experiments revealed differences in species‐specific toxicity only until 10 min after mucus production.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mutualisms typically involve organisms that provide food and shelter in return for protection from predators and competitors. Corals, for example, provide shelter and food to herbivorous fish in return for protection from enemies such as seaweeds (Dixson and Hay 2012). Ant nests are safe environments with ample of food sources and are consequently targeted by many organisms (Kronauer and Pierce 2011).…”
Section: Introductionmentioning
confidence: 99%
“…The possibility of tritrophic mutualisms involving plant volatiles has received considerable attention in terrestrial communities (2-5); however, similar interactions have rarely been suggested for marine systems (6). Dimethyl sulfide (DMS) and its precursor dimethylsulfoniopropionate (DMSP) are well-established infochemicals in the marine environment, and as such are good candidate molecules for mediating tritrophic interactions between phytoplankton and carnivores (7)(8)(9)(10).…”
mentioning
confidence: 99%